Innovative directions of CKD prevention and treatment - Kolesnyk, M. (Ukrainian Journal of Nephrology and Dialysis, 2019)
Chronic kidney disease (CKD) is global challenge of health-care. Existence of CKD significantly increases total lethality risk as well as cardiovascular mortality risk. The issue is that current methodology does not ensure prevention, early detection of CKD and avoidance of it progression. Innovative patient-oriented approaches for solution of these issues must be realized through implementation of national screening programs, IT CKD self-testing, development of CKD-oriented drugs for new therapeutic targets. If mentioned above problems will be solved, innovative modalities of prevention of steady progression of CKD and the new forms of medical care organization, at least, will help to decrease the level of CKD morbidity and decelerate it progression.